The "other" mTOR complex: New insights into mTORC2 immunobiology and their implications. Issue 6 (19th March 2019) - Dai, Helong; Thomson, Angus W.
Abstract : A central role of the mechanistic target of rapamycin (mTOR) in regulation of fundamental cell processes is well recognized. mTOR functions in two distinct complexes: rapamycin‐sensitive mTOR complex (C) 1 and rapamycin‐insensitive mTORC2. While the role of mTORC1 in shaping immune responses, including transplant rejection, and the influence of its antagonism in promoting allograft tolerance have been studied extensively using rapamycin, lack of selective small molecule inhibitors has limited understanding of mTORC2 biology. Within the past few years, however, intracellular localization of mTORC2, its contribution to mitochondrial fitness, cell metabolism, cytoskeletal modeling and cell migration, and its role in differentiation and function of immune cells have been described. Studies in mTORC2 knockdown/knockout mouse models and a new class of dual mTORC1/2 inhibitors, have shed light on the immune regulatory functions of mTORC2. These include regulation of antigen‐presenting cell, NK cell, T cell subset, and B cell differentiation and function. mTORC2 has been implicated in regulation of ischemia/reperfusion injury and graft rejection. Potential therapeutic benefits of antagonizing mTORC2 to inhibit chronic rejection have also been described, while selective in vivo targeting strategies using nanotechnology have been developed. We briefly review and discuss these developments and their implications. Abstract : This minireview describes recent progress in understanding the functional biology and immune regulatory properties of mechanistic target of rapamycin complex 2 and discusses the implications of modulation of its activity for transplantation.